Reflections on the Prospective Outcomes of Injury Study (POIS; 2006-2023): how population-based research can address Māori outcomes and governance - Wyeth, Emma H.; Derrett, Sarah (Frontiers in Research Metrics and Analytics, 2023)
Injury is a leading cause of disability. Twenty years ago, we knew financial costs of injury were high but little was known about the short, medium and long-term outcomes after injury. In 2006, a Pilot Study and engagement with Māori across the country was undertaken to discuss the planned main study to understand how best to design a study that was meaningful and beneficial to Māori and policy-makers. Between 2007–2009, 2,856 injured New Zealanders (including 20% Māori) with an Accident Compensation Corporation (ACC) entitlement claim were recruited to the Prospective Outcomes of Injury Study (POIS). Participants shared detailed information (at 3, 12 and 24 months, and 12-years post-injury) about a broad range of topics including: the injury, socio-demographics, health, health services access, employment and wellbeing. Administrative data about injury-related hospitalisations, the sentinel injury and subsequent injuries were also collected, as well as in-depth qualitative interviews. This paper focuses on the why, how and impacts of POIS, especially in relation to Māori design and approaches, capability and capacity building, and leadership. Focusing on these aspects for Māori within POIS over time has ensured delivery of findings capable of informing and improving outcomes and policy. In particular, POIS has had considerable impact, influencing ACC's research strategy and outcomes' focus, and has provided disability, health, and wellbeing outcomes knowledge previously unavailable, especially for Māori.